Modelling the oceanic circulation in the Delagoa Bight - Cossa, Obadias J (Department of Oceanography, 2018)
The ROMS is used to investigate the oceanic circulation in the Delagoa Bight region, near the southwestern end of the Mozambique Channel. The model is initially configured at a horizontal resolution of 1/10° (9.9km) over the domain 30.1-43°E,22.13-30.8° S. Subsequent configurations nested an inner grid of resolution 1/30° (3.3km) over the region 32.43-36.43°E,24.09-27.71°S Several sensitivity experiments were performed with and without the inner grid or with or without tidal forcing. Using only the outer coarse resolution grid, the first experiment (DELAGI) does not include tidal forcing whereas tides are included in the second (DELAG-II) experiment. DELAG-III and DELAG-IV both use the inner higher resolution grid but exclude and include tidal forcing respectively. The model was evaluated against observations, namely the WOA, Pathfinder SST and AVISO SSH. The results showed that ROMS adequately resolves the oceanic features in the region, namely the pathways of the anticyclonic eddies from the northern Mozambique Channel and from Madagascar, and the instances when the DBLE is present or absent. The model is also able to reproduce the main water masses and their sources in the region. Water masses found in the centre of the Bight enter through the northeastern sector, either by intrusion of pulses or instabilities of the southwards flowing current. When the DBLE is well established, upwelling is likely to contribute to the water masses in the lower layers. The transport of water towards the Bight from the east was found to be less than that from the north. The model also succeeds in representing the thermocline structure of the DBLE but it fails to capture the local salinity maximum. When tidal forcing is included, the speed of the flow close to the coast increases. The model also revealed the influence of the Inhambane Cyclone on the Delagoa Bight as well as on the region to its south. This cyclone, which is generated in the flow near Inhambane, is similar to Natal Pulses which occur in the Agulhas Current. An eddy detecting and tracking system was used with both the model outputs and VISO SSH to determine the statistics of the DBLE, namely its dimensions, amplitudes and life-times. A maximum radius of 59.52 km, life span of 126 days and an amplitude of 27.27 cm were found. It was also demonstrated that this feature is generated northeast of the Bight. When the inner grid was included in the simulations, anticyclonic features were generated within the Bight with a maximum diameter of 85.4 km and life span of 12 day. These anticyclonic features dominate the circulation when the DBLE is absent (less than 30 percent of the total period of the simulation). The possibility of several cyclonic cores existing simultaneously in the Bight was also demonstrated. Two cores were found with life spans of more than 12 days. When the number of cores is greater than two, they tend to be short lived. Analysis of energy conversion rates showed that the generation of both the DBLE and the Inhambane cyclones is mainly by barotropic instabilities, although in both regions of their generation, weak baroclinic instabilities were also found.